EFEKTIFITAS METODA VAKSINASI FLEXIBACTER PADA BENIH IKAN KERAPU MACAN, EPINEPHELUS FUSCOGUTTATUS DI HATCHERI - Johnny, Fris; Roza, Des; Zafran, Zafran (BERITA BIOLOGI, 2014)
Vaccination is one of the approaches against infectious diseases in cultured marine fish. The purpose of this study was to evaluate the effectiveness of Flexibacter vaccine in juvenile of tiger grouper (Epinephelus fuscoguttatus). Nine hundred of tiger grouper with total length of 7-8 cm reared in nine concrete tanks. For each three tanks, fishes were vaccinated with injection, immersion, and without vaccination as control. Booster was delivered at 10 and 30 days after first vaccination. Challenge test with live Flexibacter bacteria was performed 90 days post vaccination. Observations were made on clinical symptoms and survival rates which presented in relative percentage survival(RPS).The experiments were performed in completely randomized design with three replicates. The data then analyzed with ANOVA. The results showed that the antibody titer values of vaccinated fish were higher then unvaccinated fish, namely 128 for injection, 64 for bathing and 4 for control. Survival rates of vaccinated fish following challenged test were higher than control and significantly different (P<0.05), i.e. 88.67% (with RPS of 60%) for injection and 83.33% (with RPS of 50%) for immersion and 66.67% for controls. It is suggested that Flexibacter vaccine administered through injection and bathing are effective to increase immunity of tiger grouper against Flexibacter infection